KAJIAN RANTAI PASOKAN DAN PENGANEKARAGAMAN KONSUMSI PANGAN BERBASIS PRODUK UMBI-UMBIAN : STUDI KASUS JAWA BARAT - Heny Sukesi (Trade Analysis and Development Agency, Ministry of Trade of Republic of Indonesia, 2010)
Supply chain of tubers research in West Java purpose to study accelerating consumption diversification based local content food, especially tubers product. According to industrial cluster and one village one product (OVOP) approach chose 5 regency in West Java as research region. West java has potentially tubers are cassava and sweet potato. The cassava production in West Java annually achieves 2 million tones, whereas its potential production approximaly 4 million tones. The production of sweet potato in West Java achieves 390 thousand tones, whereas its potential production about 700 thousand tones. The cassava production at 5 regency overall more than 1 million tones, whereas its potential production can reach almost 2 million tons a year. The sweet potato production at 5 regency overall is 220 thousand tones, whereas its potential production is 350 thousand tons a year. According to potency of production as mention above, the tuber supply chain in West Java has already builded on traditional chain, either that begin from small farmer (the holder of limited farm) or large farmer/trader which those managed through developing distribution line. It in line with product diversification including tuber flavor and other tuber product. In the future,the tuber product development will give big the market opportunity either for trader/farmer or other related stakeholder.